Role of Nitrogen Fertilizer on Cadmium Uptake by Ramie (Boehmeria nivea (L.) Gaudich) Grown on Cadmium Contaminated Soil - Reginawanti Hindersah; Anne Nurbaity; Dedi Nursyamsi (Fakultas Pertanian Universitas Padjadjaran, 2015)
ABSTRACTContinues phosphate fertilization as well as organic matter amendment can increase cadmium concentrationin soil and induce more cadmium uptake by plants. Pytoremediation using non edible plant such as ramie(Boehmeria nivea L. Goud) is cheap and effective method to extract Cd from Cd-contaminated soil. Since inplant tissue Cd is bound in phytochelatin peptide which contains nitrogen and sulphur, the objective of thisgreen house experiment was to assess the influence of nitrogen fertilizer in form of urea on cadmiumuptake, nitrogen and sulphur concentration in shoots as well as shoot dry weight of 60-day old ramiegrown in cadmium-contaminated soil. The experiment was set up in a Split Plot Design with two treatmentsand three replications. The main plot was cadmium levels (0, 10 and 15 mg kg-1) and subplot was urea level(0, 5.0 and 7.5 g pot-1). The result showed that the increase of cadmium concentration in soil enhanced itsconcentration in ramie shoot regardless of urea levels. However either cadmium or urea did not changesulphur concentration in ramie shoot. Urea of 7,5 g/pot increased shoot dry weight but adding CdCl2.H2O of15 mg/kg did not change shoot dry weight. This experiment demonstrated that ramie was able to grow inrelatively high level of soil cadmium, and higher cadmium uptake by ramie shoot was not followed by anincrease in nitrogen as well as sulphur uptake.Keywords: Cadmium, Urea, Nitrogen, Sulphur, Ramie.